Enhancing Students Lower Mathematics Cognitive Ability Using Multi-Representation Discursive Model Assisted by Realistic Mathematics Education Approach in Elementary School - Tri Yuliani; Shely Cathrin (Al Ibtida: Jurnal Pendidikan Guru MI, 2024)
AbstractThis research addresses the problem of low cognitive mathematics ability of grade 5 students, especially on the topic of geometry. The solution is done by implementing the Multi Representation Discourse model (MRD) assisted by the Realistic Mathematics Education approach (RME). This study used a quasi-experimental design using a pretest-posttest control group framework. The study population consisted of 107 students in the Klaten coordination area, with a random sample of 44 participants. A 7-item essay-based test was used as the research instrument to measure cognitive ability.  Hypothesis testing showed a significance value of 0.047 and a gain score of 62.01%, indicating the effectiveness of MRD with the RME approach in improving mathematics cognitive ability. In addition, the mean difference of 32.28 between the pretest and posttest scores indicated a substantial improvement in students' cognitive abilities after the MRD model with the RME approach was applied.Keywords: mathematic’s cognitive ability, multi-representant discursive model, rme approach.                                                              AbstrakPenelitian ini membahas masalah rendahnya kemampuan kognitif matematika pada siswa kelas 5 sekolah dasar, khususnya pada topik bangun ruang. Solusi yang dilakukan dengan mengimplementasikan model Multi Representasi Diskursi (MRD) berbantuan pendekatan matematika secara realistik (RME). Penelitian ini menggunakan desain kuasi-eksperimental dengan menggunakan kerangka kerja kelompok kontrol pretest-posttest. Populasi penelitian terdiri atas 107 siswa di wilayah Kabupaten Klaten, Jawa Tengah dengan sampel acak sebanyak 44 peserta. Tes berbasis esai sebanyak 7 soal digunakan sebagai instrumen penelitian untuk mengukur kemampuan kognitif.  Pengujian hipotesis menunjukkan nilai signifikansi sebesar 0,047 dan gain score sebesar 62,01%, yang mengindikasikan keefektifan MRD dengan pendekatan RME dalam meningkatkan kemampuan kognitif matematika. Selain itu, perbedaan rata-rata sebesar 32,28 antara nilai pretest dan posttest menunjukkan peningkatan yang substansial dalam kemampuan kognitif siswa setelah diberlakukan model MRD dengan pendekatan RME.Kata kunci: kemampuan kognitif matematika, model diskursif multi-representatif, RME.